Indicadores de perda de solo espacializados como ferramenta de apoio à decisão para gestão ambiental integrada de bacias hidrográficas - Weiler, Elenice Broetto (2017)
In order to minimize the soil degradation (natural or anthropic), we have sought alternatives that aim to the economic development allied to the sustainable development. To produce without destroying, knowledge and planning are needed among many things. The study of erosion potential in order to diagnose areas that are more likely to soil losses (current and potential) in watershed can help to prepare preventive measures to protect the soil and others natural resources, avoiding damages to the environment and the human activities. This study was aimed to evaluate the use of the Universal Soil Loss Equation (USLE) in a spacialized way as an indicator of soil loss and the susceptibility of areas to the potential erosion; to verify how sensitive the model`s response is to the calculation of rainfall erosivity and the uncertainty in the values of the model parameters in different land use scenarios; as well as to propose a methodology for the use of this tool to support the decision on integrated environmental management of river watershed. The model of the potential erosion loss calculus used was based on the Universal Soil Loss Equation (USLE) of Wischmeier and Smith (1978), with the aid of a Geographic Information System, ArcGis 10.2.1 software, where the factors of soil, rainfall, relief, soil use and conservation practices were spacialized for the total drainage area of the watershed. The study area is located in the Ibicuí River Watershed at the geographic coordinates 29°00' and 29°30' South latitude and 53°39' and 54°06' West longitude with a total drainage area of 1541.9 km2. It is inserted in the zone of transition between Central Depression and the Sul-Riograndense Plateau characterized by shallow soils to very deep, with predominance of Entisol U.M. Guassupi (48.9%), with flat relief to very mountainous, being drained by the Toropi River, which encompasses the municipalities of Tupanciretã, Quevedos, Júlio de Castilhos and São Martinho da Serra. Soil losses were calculated for the current use situation of the watershed soil as well as for 32 elaborated scenarios with combinations of different equations to calculate the R factor (Rufino et al., 1993; Cassol et al., 2007 and Santos, 2008) and different land use situations. Then, in function to the result, the areas were classified by erosion bands according to Ribeiro's methodology, 2006. The largest area percentages for the current use scenario are located in the class of 1-10 t.ha-1.ano-1, classified as having low erosive potential. Those classified as mean potential loss of soil in the watershed are in the order of 38.5; 32.1; 24.7 t.ha-1.ano-1 for the different R equations, which shows a low to moderate erosive character in this watershed. Comparing the different simulated scenarios, the analysis was based on the observation of the differences in the distribution of watershed areas between the classes of potential soil loss. In relation to the influence of the C factor (soil use) on soil loss rates, it highlights that the use of native forest provides the lowest losses, followed by Agriculture in the SPS system (Soybean/Pasture/Soybean) and later on Forest/Reforestation in all scenarios tested with these uses. Using the model, an application strategy was designed to identify suitable areas for each type of use, such as support for the land use planning. Considering the current use, among the criteria adopted for tolerance to soil loss, it was identified that: 56.48% of the watershed area needs revision of the soil use, here called planning, when considered the criterion of up to 10 t.h-1.ano-1; 21.58% for the criterion of up to 50 t.h-1.ano-1 and 12.44% for the criterion of up to 100 t.h-1.ano-1. As a prognostic of land uses, it is estimated that 810.62 km2 of the watershed area will serve for Agriculture - SPS and 328.61 km2 for Forest./Reforestation when adopted a limit of potential soil loss of 10 t.h-1.ano-1. In conclusion, the spatialized USLE model allows the identification of susceptible areas to potential soil losses, being possible to quantify and spatialize the areas in accordance with limits of potential soil loss and also those that do not tolerate the use of the soil tested. It allows to plan areas according to the definition of a tolerable limit of potential soil loss for a priority use and to reclassify these scenarios based on this limit. In addition, the USLE model adapted to GIS has proved to be a robust and sensitive tool in the differentiation of potential erosions between areas with different soil uses, different soils and different slopes, and it is possible to create varied maps for this studied watershed, providing useful information for decision makers who can prioritize and implement the better management practices to reduce the erosion load.